Political connection, foreign institutional investors and tunneling: evidence from Indonesia - Nuraina, Elva; Nasih, Mohammad; Agustia, Dian (Business: Theory and Practice, 2022)
The purpose of this study is to examine the moderating effect of foreign institutional investors on the relationship between political connection and tunneling. To achieve this goal, our study has examined all companies listed on the Indonesia Stock Exchange between 2015 and 2019, and obtained 1,571 firm-year observations. By using a quantitative approach and data analysis using moderated regression analysis, the results of this study indicate that foreign institutional investors play a role in weakening political connections to tunneling. This shows that foreign institutional investors have a role in reducing tunneling. These investors influence the behavior and performance of the company, so, even though the company has political ties, foreign institutional investors are less susceptible to political pressure and are more likely to negotiate to enhance the interests of minority shareholders, and protect their reputations. This finding has important implications for regulators to consider when evaluating the Investor Protection Act, in particular the protection of minority shareholder rights in companies with political ties.